2016
DOI: 10.11599/germs.2016.1089
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density and associated risk factors in HIV-infected patients

Abstract: At lumbar spine DEXA, male gender was statistically associated with reduced BMD. At the left hip Ward's area, decreased BMD T scores were significantly associated with aging. The reduced BMD was higher in patients receiving PI- or NNRTI-containing regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
4
17
2
Order By: Relevance
“…A comparable prevalence in reduced BMD (23%) was found by Cardeal et al (2017) among 108 individuals living with HIV in Brazil [23]. However, some studies have reported higher prevalence rates of reduced BMD ranging from 37% to 80% among PLWHIV [18][19][20]35]. A slightly lower prevalence in reduced BMD revealed in this study could be due to the age group of participants.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A comparable prevalence in reduced BMD (23%) was found by Cardeal et al (2017) among 108 individuals living with HIV in Brazil [23]. However, some studies have reported higher prevalence rates of reduced BMD ranging from 37% to 80% among PLWHIV [18][19][20]35]. A slightly lower prevalence in reduced BMD revealed in this study could be due to the age group of participants.…”
Section: Discussionsupporting
confidence: 80%
“…Higher prevalence rates of up to 85% of low BMD among PLWHIV in low and middle income countries have been reported by a number of studies [18][19][20][21][22]. Apart from ART, factors such as lack of physical activity (PA), lower body mass index (BMI), female sex, older age, nutritional deficiencies of calcium and vitamin D, depression, contraception use, smoking and alcohol use are believed to contribute to high prevalence of low BMD among PLWHIV [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with other reports from South-Eastern Europe [5,6,32]. Chiţu-Tișu and colleagues observed a similar prevalence of reduced BMD (17% osteoporosis and 48% osteopenia) in 60 HIV-infected patients in Romania.…”
Section: Discussionsupporting
confidence: 93%
“…Chiţu-Tișu and colleagues observed a similar prevalence of reduced BMD (17% osteoporosis and 48% osteopenia) in 60 HIV-infected patients in Romania. They noted that patients with more prolonged exposure to non-nucleoside reverse transcriptase inhibitors were at higher risk of low BMD [6]. Another group noted a 47% prevalence of low lumbar BMD in Romanian patients, together with a relatively high prevalence of chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, HIV-infected infected subjects have lower BMI than HIV-negative control groups, as described previously 22 . Several reports demonstrated that habit of smoking, and lifestyle, traditional known risk factors for osteoporosis, are also important in this population 23 , 24 .…”
Section: Discussionsupporting
confidence: 76%